Vzdrževanje izdelovalne opreme - Drstvenšek, Igor; Ulaga, Samo (University of Maribor Press, 2020)
Maintenance of Manufacturing Equipment. The aim of the textbook Maintenance of Manufacturing Equipment is to present and explain methods for ensuring the availability of machinery and equipment, notably through methods of identifying failure mechanisms and break-downs. The basic failure mechanism of moving parts of machinery is definitely wear to which the introductory part of the textbook is devoted. It also presents the theory of lubrication as a method of reducing friction wear. The second part of the textbook is devoted to diagnostic methods, which are used in preventive maintenance. Of particular interest is the method of vibro-acoustic analysis, which is used in predictive maintenance and is covered in the central part of the textbook. It presents the ways of recording and analyzing vibro-acoustic signals and the practical application of vibro-acoustic analysis on typical cases of machine elements. The final part of the textbook presents methods for repairing and replacing components and overhauling of machine tools.